The main principles of the structural organization of the immune system of the Japanese quails - S B Seleznev; E A Krotova; G A Vetoshkina; E V Kulikov; L P Burykina (RUDN Journal of Agronomy and Animal Industries, 2015)
According to the received results, the organs of the immune system of quails represent anatomically diffused but strategically distributed protective network: central - situated in well-protected places (thymus, bursa cloacalis), and peripheral - situated at the border of the organism with the environment (glandula palpebral tertius, lymphoid cecal tonsil and lymphoid diverticulus) and on the routes of blood circulation (spleen). They are indicators that inform the immune system of the organism about the antigenetic diversity of the environmental microflora, that should be taken into account while planning anti-epizootical measures during vaccination of birds in order to create the immunity against infectious diseases.